Vein of Galen aneurysm. Issue 2 (May 2016) - Mohan, Reena; Nayyar, Roshini; Ryder, Lynette; Lord, David; Athayde, Neil
Abstract: Background : AV malformation of the vein of Galen, also known as vein of Galen aneurysm, is an intracranial anomaly characterised by a midline, high flow lesion with a complex vascular architecture. It compromises less than 1% of all cerebral arteriovenous malformations seen in adults and children. Timely diagnosis of the malformation is of importance particularly during the perinatal period due to the large systemic shunting within the fetal brain potentially leading to cardiac failure, hydrops and perinatal death. Method : Case Report: In this report, we present a case that had an increased nuchal translucency of 6 mm at 12 weeks gestation (karyotype normal), nuchal oedema of 12 mm noted at morphology scan and subsequently diagnosed with vein of Galen malformation at 32 weeks on a follow up scan. It was evaluated further with 3D power Doppler imaging modality. 3D power Doppler imaging provided us with improved images of the malformation in utero which was helpful for characterising the vascular anatomic features of the lesion before planned delivery and neonatal treatment. Results : The patient was followed up with antenatal ultrasounds. There was no evidence of hydrops. She delivered a live healthy infant weighing 2.8 kg by elective caesarean section at 39 weeks. The child is now five and half years old and has undergone embolisation twice. Conclusion : We present a case illustrating use of Power Doppler imaging in a vein of Galen malformation. Prenatal diagnosis and endovascular treatment in the early neonatal period is important in preventing heart failure and resultant mortality in vein of Galen aneurysm.